2016
DOI: 10.5038/1827-806x.45.3.1978
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of antimicrobial activity of culturable bacteria isolated from Krubera-Voronja Cave

Abstract: In the present study we aimed to perform the first analysis of antimicrobial activity of bacteria isolated from Krubera-Voronja Cave, with the main focus on their activity against Grampositive bacteria, including Gram-positive pathogens. Using five different media, in total 874 heterotrophic cultures were isolated from water and sediment samples collected in Krubera-Voronja Cave at a depth from 220 m to 1640 m. 14.0% of all isolates demonstrated antibacterial activity against Gram-positive and Gram-negative te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…Phenotypic antibacterial activity of these strains against the test strains of Micrococcus luteus Sar1, Bacillus thuringiensis TL8, Escherichia coli BL21(DE3), and Pseudomonas sp. VR1 was determined previously (Klusaite et al, 2016). For the current work, three groups of Krubera–Voronja Cave bacterial strains were chosen: 54 strains without phenotypic antibacterial activity (a test group), 27 strains with phenotypic antibacterial activity (a control group), and 10 randomly selected strains with unknown antibacterial activity.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Phenotypic antibacterial activity of these strains against the test strains of Micrococcus luteus Sar1, Bacillus thuringiensis TL8, Escherichia coli BL21(DE3), and Pseudomonas sp. VR1 was determined previously (Klusaite et al, 2016). For the current work, three groups of Krubera–Voronja Cave bacterial strains were chosen: 54 strains without phenotypic antibacterial activity (a test group), 27 strains with phenotypic antibacterial activity (a control group), and 10 randomly selected strains with unknown antibacterial activity.…”
Section: Methodsmentioning
confidence: 99%
“…Genomic DNA was extracted from fresh grown cultures using the GeneJET Genomic DNA Purification Kit (Thermo Fisher Scientific, Waltham, MA, United States). BOX-PCR was performed as described in Klusaite et al (2016). Products of amplification were analyzed by electrophoresis using 1% agarose gel.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The percent of cultures that showed antibiosis to indicator bacteria using the cross-streak method ranged from 8.62% to 21.1%. A study from a cave in the Western Caucasus [26] showed 14% of 87 isolates produced antimicrobials. The proportion increased with sampling depth into the cave, and was highest in the most remote lower levels of the cave.…”
Section: Discussionmentioning
confidence: 99%